IDENTIFIKASI KARAKTER PERMUKIMAN DI TIGA WILAYAH PEMBANGUNAN KABUPATEN BADUNG - Krisnandika, Anak Agung Keswari; Yusiana, Lury Sevita; Dharmadiatmika, I Made Agus; U’Zal, Mar’ie Abda (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 1 (2020): Vol. 14 No. 1, 2020, 2020)
Badung Regency is a rapidly development area in Bali Province that caused by highly human activities. This development can be seen from the character of settlements in the are. Badung regency is divided into 3 development areas namely North Badung (sub-District Petang and Abiansemal), Middle Badung (sub-District Mengwi) and South Badung (sub-District Kuta Selatan, Kuta and Kuta Utara). The survey results on biophysical factors such as vegetation, land use, landforms and human factors i.e. land boundaries, patterns, infrastructure, and regional policy show that there are some different unique characteristics between these 3 development areas in Badung Regency. In general, landscapes of settlement in the North Badung are composed of linear housing along the main road but between houses tend to be separated by plantation area. Landscapes of settlement in the Middle Badung, consist of clustered housing along the road, with small access to the back of the house (rice fields) while, houses along the main road in the South Badung are shophouses and the residents' houses are clustered linear along small alley.